2008
DOI: 10.1148/radiol.2461062179
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Chronic Myocarditis at Cardiac MR: Diagnostic Accuracy and Association with Immunohistologically Detected Inflammation and Viral Persistence

Abstract: In patients clinically suspected of having CMC, increased gRE and ER indicating inflammation were common findings that could be confirmed at immunohistologic analysis, whereas LE had low sensitivity and accuracy. Cardiac MR imaging may be helpful in detecting intramyocardial inflammation noninvasively, but it fails to depict viral persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
196
7
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(229 citation statements)
references
References 30 publications
14
196
7
12
Order By: Relevance
“…It was shown that early enhancement changes are detectable soon after the clinical onset of disease and vanish with declining symptoms at follow-up (121). Two studies from independent working groups have shown that sequences that assess edema and hyperemia are more sensitive, while late enhancement imaging is more specific for the diagnosis of myocarditis (117,118). This is in accordance with the current understanding of pathophysiology.…”
Section: Myocarditissupporting
confidence: 54%
See 2 more Smart Citations
“…It was shown that early enhancement changes are detectable soon after the clinical onset of disease and vanish with declining symptoms at follow-up (121). Two studies from independent working groups have shown that sequences that assess edema and hyperemia are more sensitive, while late enhancement imaging is more specific for the diagnosis of myocarditis (117,118). This is in accordance with the current understanding of pathophysiology.…”
Section: Myocarditissupporting
confidence: 54%
“…• T1-weighted early contrast-enhanced sequences assess myocardial hyperemia and capillary leak (116); • T2-weighted sequences assess myocardial edema (117,118); and • Late enhancement assesses cardiomyocyte necrosis or fibrosis (119,120). Therefore, a comprehensive in vivo assessment of tissue pathology is possible, beyond the analysis of myocardial volumes and function.…”
Section: Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, regions of myocarditis are reported to correlate closely with regions of abnormal signal on cardiac MRI. 7,8 The lack of consensus regarding the value of invasive studies such as endomyocardial biopsy and the overall good prognosis for patients with mild, acute dilated cardiomyopathy who have suspected myocarditis have led to recent recommendations that endomyocardial biopsy should be considered on the basis of the likelihood of finding specific treatable disorders. …”
Section: Definitionmentioning
confidence: 99%
“…2): 1) a regional or global myocardial signal intensity (SI) increase on T2-weighted (T2w) images, 2) an increased global myocardial early gadolinium enhancement ratio (EGEr) between myocardium and skeletal muscle in gadolinium-enhanced T1-weighted (T1w) images, and 3) at least one focal lesion with non-ischemic regional distribution in inversion recovery-prepared gadolinium-enhanced T1w images (late gadolinium enhancement, LGE). The SI increase on T2w images can either be analyzed visually or can be quantified by an SI ratio of myocardium over skeletal muscle of ≥ 1.9 ("T2-ratio" / "edema ratio") [22,23]. The largest to date meta-analysis dealing with the T2-ratio showed an average sensitivity of 70 % and an average specificity of 71 % for detecting myocardial edema [21].…”
mentioning
confidence: 99%